Inovasi Pengelolaan Sampah Melalui Budidaya Maggot Black Soldier Fly sebagai Peningkatan Ekonomi dan Perilaku Pro Sosial Warga RW 07 Jatisari Kota Bekasi - Gufron Amirullah; Agus Pambudi Dharma; Nur Asiah (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: The community of RW 07 Jatisari Village Bekasi City produces organic waste that has not been managed properly and is still disposed of in the trash. This training activity aims to increase the knowledge and experience of the RW 07 community in processing organic waste using black soldier fly larvae which can increase community income and a clean environment. Method: The activity will be held on November 21 - 28, 2022, at RW 07 Jatisari Village, Bekasi City. The process of training activities is in two ways: the provision of training materials and assistance at each stage of maggot cultivation. Participants were asked eight questions before and after the training, and then the data was analyzed descriptively. Result: The community has increased knowledge that organic waste can damage the environment, producing methane gas. Organic waste that accumulates will rot, becoming a breeding place for bacteria carried from intermediate animals (vectors) that can cause diseases such as dysentery, hepatitis A, and bubonic plague. Conclusion: BSF can be sold, generating additional income for the community.